SCROL Strategy and Reading Comprehension Achievement: A Quasi-Experimental Study of Seventh-Grade Students in Indonesia - Ulandari, Fuspita; Astrid, Annisa; Salsabila, Mirrah (LPPM Universitas Jambi, 2026)
This study investigates the effect of the SCROL (Survey, Connect, Read, Outline, Look Back) strategy on the reading comprehension achievement of seventh-grade students at SMP Negeri 2 Tanjung Batu, Ogan Ilir, Indonesia. Many junior high school EFL students in Indonesian contexts continue to struggle with identifying main ideas, interpreting supporting details, and engaging independently with written texts challenges inadequately addressed by the Project-Based Learning (PBL) approach currently mandated under the Merdeka curriculum. This study aimed to determine whether SCROL instruction significantly improved students' reading comprehension and whether a significant between-group difference existed compared to conventional instruction. A quasi-experimental non-equivalent control group design was employed with 60 seventh-grade students (experimental: n=30; control: n=30). Data were collected through validated and reliable multiple-choice reading comprehension pre-tests and post-tests. Paired samples t-tests confirmed significant within-group improvement in the experimental group (t = −28.016, p = 0.000), and independent samples t-tests confirmed a significant between-group difference in post-test scores (t = 11.600, p = 0.000). These findings demonstrate that the SCROL strategy is an effective, structured instructional approach for junior high school EFL learners. English teachers are encouraged to integrate SCROL explicitly into reading instruction, particularly in contexts where students lack strategic comprehension frameworks.